Testing risk management decision making competency of project managers in a crisis - Strang, Kenneth David; Vajjhala, Narasimha Rao (The Journal of Modern Project Management, 2022)
The objective of the current study was to use a rigorous controlled experiment simulating a project failure to measure how cognitive bias and competency impact a PM’s risk management decision making in a crisis while controlling for other project and firm level variables including lying or faking responses. The MANOVA, repeated measures ANOVA controlled experiment and post-hoc analysis techniques were rigorous because the study took place in approximately the same point in time and each participant received all treatments. The 24 respondents in these repeated measures experiment outperforms most psychology factorial research design, which would require a 4 x 24 = 96 sample size to accommodate 3 treatments and a control group. We found bias significantly impacted PM risk management decision making in a crisis, but certification and competency resulted in the best decisions. Generalizations are cautioned due to the exploratory nature of this study. However, the literature review and methods were articulated well enough to encourage replications and extensions by other researchers.